The Impact of Skill Mismatch on Earnings Losses after Job Displacement - Simon Wiederhold; Ljubica Nedelkoska; Frank Neffke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
The long-term earnings losses of displaced workers are substantial. We investigate the role of post-displacement occupational matching in explaining the cost of job displacement. We combine German administrative data on the work history of displaced workers with information on the task content of more than 260 occupations, providing a measure of skill mismatch between a worker's pre- and post-displacement occupation. We find that displaced occupational switchers suffer average wage losses of more than 8% over 15 years. However, displaced workers moving to occupations where they are initially underqualified quickly manage to return to their pre-displacement earnings path, and even gain from switching in the long run. Our preliminary results suggest that policy should encourage the requalification of displaced workers to occupations that are more skill demanding than their pre-displacement occupations.
Keywords: J24; J31; J65; 330